2020
DOI: 10.26740/jrba.v2n2.p77-81
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Condition of Coral Reef Covering in Pramuka Island Waters, Seribu Islands using Line Intercept Transect (LIT) Method

Abstract: The coral reef ecosystem is one of the typical tropical ecosystems with high biodiversity which has an important role both biologically, ecologically, physically as well as socially and economically. Several coral reef areas in Indonesia were reported to have suffered damage, not only due to climate change which has an impact on rising sea surface temperatures and ocean acidification but also due to anthropogenic factors and irresponsible management of marine tourism. This study aimed to analyze the condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…As a comparison, the coral reef in the north part of Panggang Island had a live coral cover of 27.2% (Prasetyo et al, 2018). Pramuka Island had a live coral cover of 72.38% (Permana et al, 2020). Kelapa Island had a live coral cover of 55.83% (Mutahari et al, 2019).…”
Section: Results and Discussion A Coral Reef Coveragementioning
confidence: 99%
“…As a comparison, the coral reef in the north part of Panggang Island had a live coral cover of 27.2% (Prasetyo et al, 2018). Pramuka Island had a live coral cover of 72.38% (Permana et al, 2020). Kelapa Island had a live coral cover of 55.83% (Mutahari et al, 2019).…”
Section: Results and Discussion A Coral Reef Coveragementioning
confidence: 99%
“…Both are important in contributing to fisheries, as indicated by the presence of chlorophyll-a and phytoplankton in their waters [24]. Although on Pramuka Island, most people work as fishermen, on the other hand, the tourism sector, with the attractiveness of coral reefs, is an important aspect of the Pramuka Island community [25]. The present study revealed that the physicochemical parameters of various sampling sites in Pramuka Island showed conditions that were not significantly different for physical factors but had differences in their nautical content, namely nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Jika suatu ekosistem terumbu karang sehat, maka semakin beragam dan kaya biota yang hidup di ekosistem tersebut (Cappenberg & Akbar, 2020). Berbagai survei menunjukan bahwa tutupan karang hidup rata-rata menurun secara berkala dikarenakan gangguan maupun ancaman lebih cepat mempengaruhi dibandingkan dari tingkat pemulihannya (Permana et al, 2020). Namun demikian, upaya rehabilitasi dan meningkatnya kesadaran masyarakat terhadap pentingnya ekosistem terumbu karang menjadi optimisme dalam peningkatan kondisi terumbu karang baik secara kualitas maupun kuantitas.…”
Section: Pendahuluanunclassified